PERANAN SEKTOR LUAR PERTANIAN TERHADAP KESEMPATAN KERJA DAN PENDAPATAN DI PEDESAAN BERBASIS LAHAN KERING - A. ROZANY NURMANAF (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Work opportunity and household income are two important indicators in village economicdevelopment. The purpose of analysis focuses in identifying non agricultural sector roleon two indicators in dry land village area. Data from Patanas 2004 included six provinces,these are Lampung, West Java, Central Java, East Java, South Sulawesi and West NusaTenggara is the main source of information in the analysis. The results show thatagricultural sector is dominant source of household income in dry land villages. Highproportion in household labor force who are absorbed in agricultural sector affect to theirworking hours and followed by their income from that sector. Higher in household incomelevel tend to higer in skewness level of their distribution. While, income stability relate toincome source domination. In the area where agricultural sector (especially food crops) isthe main source income, monthly income proportion fluctuate more. Conversly, in the areawhere non agricultural sector is the main source of income, monthly income proportionwill be distribute and fluctuation level is lower. Non agricultural activity, generally can bedone any time a whole the year.